The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1109/jlt.2012.2201209
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Nonlinear and PMD Impairments by Bit-Synchronous Polarization Scrambling

Abstract: Abstract-Our statistical study by the importance sampling method shows that a significant performance improvement may be achieved by bit-synchronous polarization scrambling in the presence of polarization mode dispersion and fiber nonlinearity in dispersion managed, single-channel, or wavelengthdivision-multiplexed NRZ 10 Gbit/s fiber optic transmission systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore in non-DM QPSK systems the main effect of nonlinearity is the shift of the mean value of the PMD-induced PDF of the output Q factor. This is in contrast with the case of OOK systems in the presence of in-line DM and without PMD compensation, where it was shown that nonlinearity may strongly affect the width of the Q factor PDF as well [9]. Let us briefly discuss the dependence of the Q factor PDF in the presence of nonlinear cross-talk or XPolM from the two adjacent channels.…”
Section: Simulationsmentioning
confidence: 90%
See 3 more Smart Citations
“…Therefore in non-DM QPSK systems the main effect of nonlinearity is the shift of the mean value of the PMD-induced PDF of the output Q factor. This is in contrast with the case of OOK systems in the presence of in-line DM and without PMD compensation, where it was shown that nonlinearity may strongly affect the width of the Q factor PDF as well [9]. Let us briefly discuss the dependence of the Q factor PDF in the presence of nonlinear cross-talk or XPolM from the two adjacent channels.…”
Section: Simulationsmentioning
confidence: 90%
“…In practice it is not possible with simple Monte-Carlo simulations to accurately numerically evaluate the PDF of the BER, since in order to evaluate its tails one would need a prohibitively large number of simulations. On the other hand, the tails of the PDF can be computed with just a few thousands of simulations by the IS technique [8], [9].…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…4,13 The influence mitigation of PMD can also be done by including polarization scramblers (PSs) in certain sections of the optical path, whose role is to statistically suppress the influence of PMD or to increase the influence of polarization mode coupling (in today's modern fibers, this feature is introduced in the production of optical fibers). 13,14 Another possibility to avoid the influence of PMD (and not only PMD) is the use of system margin. If there is sufficient reserve transmission capacity, the optical signal can be rerouted along a different (backup) path.…”
Section: Compensation In Optical Domainmentioning
confidence: 99%